Matura Point, East Coast, Trinidad - (:unkn) unknown (F.P.Bruce-Austin, Trinidad, 2009)
The landscape of Matura Point is typical of Trinidad's north east coast. Unsheltered, the coastline is subjected to the Trade Winds coming off the Atlantic causing the terrain to be bombarded by waves which erode it constantly giving the area its rugged shoreline.
Colour; Sepia; Style: Portrait; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Cities and towns--Trinidad and Tobago--Matura; Waves; Coasts--Trinidad and Tobago; Seashore--Trinidad and Tobago